Pengaruh E-wom dan Brand Reputation Terhadap Kepuasan Tamu Menginap di Harris Resort Barelang Batam - Hikmal akbar; Rian Surenda; Fran Serano Andres; Pasaribu Pasaribu (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2026)
The impact of brand reputation (X2) and electronic word-of-mouth (X1) on guest satisfaction (Y) at HARRIS Resort Barelang Batam is the main topic of this study. It uses a causal-associative method in a quantitative descriptive design. One hundred respondents who have visited the hotel at least twice make up the sample. Electronic word-of-mouth (X1) is classified as "very good" according to descriptive analysis results. (mean: 4.25), Brand Reputation (X2) is in the "very good" category (mean: 4.28), and Guest Satisfaction (Y) is also in the "very good" category (mean: 4.30). Data analysis was done with R-squared, t-statistics, and p-values were employed in hypothesis testing, as well as descriptive statistics and SEM-PLS. The results show that: (1) Guest satisfaction is significantly impacted by electronic word-of-mouth (t = 2.121); (2) Guest satisfaction is significantly impacted by brand reputation (t = 9.871); and (3) Guest satisfaction is significantly impacted by both brand reputation and electronic word-of-mouth, with an R-squared value of 0.684. These findings demonstrate that Electronic Word of Mouth contributes to guest satisfaction through social media reviews, while a strong brand reputation fosters trust, confidence, and positive perceptions of the hotel. When a hotel maintains a positive image, consistent service quality, and reliability, guests experience greater satisfaction with their stay at HARRIS Resort Barelang Batam.